Achievement of Height and Weight Based on Family Characteristics as Early Detection of Nutritional Disorders in Toddlers - Sari, Pety Merita; Dewi, Ayu Rosita; Frafitasari, Dika Yanuar (Universitas Islam Lamongan, 2022)
Achievement of optimal height and weight of toddlers in their growth is very necessary to improve and determine the quality of human resources in the future. Many factors affect this achievement, one of which is external factors, namely family characteristics (mother's age, family income, mother's employment status, mother's education and number of children). This study aims to determine the achievement of children's height and weight based on family characteristics (mother's age, family income, mother's employment status, mother's education and number of children).This type of research is an analytic survey, with a cross sectional observation design. The sampling technique used was Total Sampling. The sample size in this study was 45 respondents. This research was conducted in January-March 2022. Statistical analysis used in this study was the Pearson Chi-square test.Based on the results of statistical tests, the correlation coefficient table shows that the mother's age, p value = 0.242, mother's education level, p = 0.018, number of children, p = 0.552, mother's work status, p = 0.183, and family income, p = 0.022. The conclusion in this study is that there is a relationship between mother's education level and family income with the achievement of toddler height and weight, there is no relationship between maternal age, number of children and mother's work status with achievement of toddler height and weight. It is recommended to mothers who have toddlers to pay more attention and monitor the growth process of their children.